2004
DOI: 10.1046/j.1540-8167.2004.04072.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for ST Depression Associated with Contiguous Subendocardial Ischemia

Abstract: ST depression at the epicardium appears over a lateral boundary between healthy and ischemic tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
75
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 16 publications
14
75
0
Order By: Relevance
“…Cell swelling and the decoupling of gap junctions alter the microscopic structure of tissue and, hence, its passive electrical conductivity, and this change in conductivity will alter the volume conductor and thus the epicaxdial potentials. A recent modelling study by HOPENFELD et al (2004; showed that the electrical anisotropy ratio of cardiac tissue and changes in its electrical conductivity influence the distribution of epicardial potentials.…”
mentioning
confidence: 99%
“…Cell swelling and the decoupling of gap junctions alter the microscopic structure of tissue and, hence, its passive electrical conductivity, and this change in conductivity will alter the volume conductor and thus the epicaxdial potentials. A recent modelling study by HOPENFELD et al (2004; showed that the electrical anisotropy ratio of cardiac tissue and changes in its electrical conductivity influence the distribution of epicardial potentials.…”
mentioning
confidence: 99%
“…We let ∆φ p = −30 mV [1,7], and then initially set λ t = 0.01 ∀t, to give a narrow border zone between the normal and ischaemic tissue. We use the same boundary conditions as in previous work [1]; that is, we assume no current flux at the boundary of the intra-and extracellular domains at the air-tissue interfaces and at the blood-air interface.…”
Section: Half-ellipsoidal Modelmentioning
confidence: 99%
“…In order to simulate both the effects of fiber orientation and changes in the effective conductivity, we developed a multi-scale modeling approach [1]- [3] . At a cellular level, the model simulates a piece of cardiac tissue and includes details such as cell geometry, gap junctions, and the specific conductivities of various electrolytes.…”
Section: A Simulation Setupmentioning
confidence: 99%
“…The model of the whole heart simulates epicardial potentials from ischemic sources and is based on the bidomain equations. The anatomical and fiber structure data underlying this model originated in the Auckland canine heart [4] and the ischemic source was a difference in the transmembrane potential between healthy and ischemic tissue of 30 mV [1]. …”
Section: A Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation